PATTERN AND CAUSALITY ASSESSMENT OF ADVERSE DRUG REACTIONS IN PEDIATRIC POPULATION IN AND AROUND KANNAUJ - Dr. Rajneesh Kumar Kamal, Dr. Suchi Jain , Dr. Parul Kamal, Dr Mohit Trivedi , Dr. Ambrish Kumar Gupta, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
To report, assess and compare Adverse Drug Reactions (ADRs) inhealthy, malnourished and low birth weight children and to perform causality assessment of reported ADRs.